Scolicidal Agents in Hydatid Cyst Surgery - Besim, H. (Hindawi Publishing Corporation, 1998)
Injecting scolicidal solutions into the hydatid cyst and packing the operative field with sponges soaked in scolicidal agents have been used to avoid dissemination of the parasite during surgery. In the first part of this invitro study, we tried to determine the scolicidal property of various agents in different concentrations and exposure times. In the second part, we tested whether sponges soaked in different type and concentrations of scolicidal agents have any role beyond being a mechanical barrier. 20% saline, 3% hydrogen peroxide, 1.5% cetrimide-0.15% chlorhexidine (10% Savlon®), 95% ethyl alcohol, 10% polyvinylpirrolidone-iodine (Betadine®) and their further dilutions were used in this study. Protoscoleces were obtained from the cyst containing livers of the sheep and viability was determined with dye-uptake (0.1% Eosin) and flame cell activity. Savlon® was found to be the least concentration dependent scolicidal agent among those studied. Scoleces sprayed on sponges soaked in 20% saline, 95% ethyl alcohol, Betadine® and 3% hydrogen peroxide were killed after 15 minutes. 3% and 10% saline and normal saline were ineffective. Sponges work not only as a mechanical barrier but also as a chemical one if the agent is chosen correctly. In purely cystic hydatid liver disease, the risk of dissemination of the cyst contents can be avoided by injection of a potent scolicidal agent such as Savlon®.